Disparities in Speech Therapy for Voice Disorders Between English‐ and Non‐English‐Speaking Patients. (9th February 2021) - Huwyler, Camille; Merchant, Maqdooda; Jiang, Nancy
Abstract : Objectives/Hypothesis: To evaluate whether language of choice affects compliance with speech therapy for voice disorders. Study Design: Retrospective chart review. Methods: A retrospective study was performed at Kaiser Permanente Northern California to compare compliance with referrals to speech therapy for voice disorders between English‐ and non‐English‐speaking patients. Patients referred from January 2012 through December 2017 were included. Logistic regression models were used to calculate the adjusted odds ratios (aOR) and to determine social and demographic factors affecting compliance. Results: Of 7, 333 patients referred to speech therapy for a voice disorder, 7, 171 were identified as English speaking and 162 as non‐English speaking. The two cohorts were similar in terms of gender and proportion over 65 years of age, although non‐English‐speaking individuals were more likely to be Hispanic or Asian than English speakers, who were more likely to be White or African American. Overall compliance was lower among non‐English‐speaking patients than English speakers (63% vs 74%) ( P  = .0011). Logistic regression showed that the need for an interpreter was significantly associated with higher noncompliance (aOR 1.56, 95% CI 1.11–2.18), as was age less than 65 and income less than the study aggregate median income. Being multiracial or having a voice disorder of neurologic origin was associated with better compliance. Conclusion: This study demonstrates significant noncompliance with speech therapy for a variety of voice disorders. This problem is exacerbated for patients who do not speak English and who are younger, of lower income, or are referred for functional voice disorders. In‐person interpreters or multilingual speech therapists may help to improve compliance. Level of Evidence: IV Laryngoscope, 131:E2298–E2302, 2021